The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/chin.200607069
|View full text |Cite
|
Sign up to set email alerts
|

Aza‐Michael Reactions Catalyzed by Samarium Diiodide.

Abstract: Aminocarboxylic acids (hydrazinocarboxylic acids) and esters P 0270Aza-Michael Reactions Catalyzed by Samarium Diiodide. -Samarium diiodide catalyzed Michael addition of aromatic amines to α,β-unsaturated N-acyloxazolidinones leads to formation of β-amino acid derivatives. Depending on the stoichiometry of the starting compounds and the nature of the amine, β-amino-N-acyloxazolidinones and/or β-amino amides are formed. This result is investigated in detail and presented in a table. -(REBOULE, I.; GIL*, R.; COL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The reaction of an open chain bulky secondary amine like diisopropylamine proceeded very well (entries 6, 7). Cyclic secondary amines such as pyrrolidine, piperidine and morpholine underwent facile additions with acrylonitrile, acrylic esters and acrylamide (entries [11][12][13][14][15][16][17]. Aromatic amines are less reactive than aliphatic amines and took longer reaction time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of an open chain bulky secondary amine like diisopropylamine proceeded very well (entries 6, 7). Cyclic secondary amines such as pyrrolidine, piperidine and morpholine underwent facile additions with acrylonitrile, acrylic esters and acrylamide (entries [11][12][13][14][15][16][17]. Aromatic amines are less reactive than aliphatic amines and took longer reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…Usually these conjugate additions are carried out in the presence of a strong base or acid [5]. To avoid this harsh conditions, a number of milder procedures have been developed over the past few years using a variety of reagents such as SnCl 4 /FeCl 3 [6], InCl 3 [7], CeCl 3 .7H 2 O-NaI [8], Yb(OTf) 3 [9], Cu(OTf) 2 [10], CAN [11], Bi(NO 3 ) 3 [12], Bi(OTf) 3 [13], LiClO 4 [14], KF/alumina [15], SmI 2 [16], Cu(acac) 2 /ionic liquid [17], ionic liquid/quaternary ammonium salt in water [18], boric acid in water [19],cyclodextrin [20], ZrOCl 2 .8H 2 O [21], borax [22], bromodimethylsulfonium bromide [23], [HP(HNCH 2 CH 2 ) 3 N]NO 3 [24], palladium [25] and nickel [26] etc. Although these methods are quite useful, many of these procedures require a large excess of reagents, long reaction time, drastic reaction conditions and toxic reagents as well as harmful solvents such as acetonitrile or 1,2-dichloroethane.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that samarium diiodide used in methylene chloride is an efficient pre-catalyst for the formation of carbon-nitrogen bonds [6]. Recently we studied samarium diiodide-catalyzed aza-Michael additions of amines onto , -unsaturated N-acyloxazolidinones which afford two products, the aza-Michael adduct 3 and the amide 4 resulting from an amidation reaction by a second equivalent of amine on the former (Scheme 1) [7]. The ratio of adducts depends on the amine but also on the substituent in the 4-position of the , -unsaturated N-acyloxazolidinone.…”
Section: Introductionmentioning
confidence: 98%
“…Among the various methods, the aza-Michael addition is a straightforward route for the generation of carbon-nitrogen bonds in the synthesis of β-amino carbonyl or nitrile compounds. Aza-Michael reaction is reportedly catalyzed by a couple of transition metal salts like InCl 3 [33], CeCl 3 •7H 2 O [34], Yb(OTf ) 3 [35], Bi(NO 3 ) 3 [36], Cu(OTf ) 2 [37], LiClO 4 [38], SmI 2 [39], FeCl 3 •6H 2 O [40], cerium(IV) ammonium nitrate [41]. Heterogeneous catalysts like SiO 2 -H 2 SO 4 [42], SiO 2 -HClO 4 [43] have also been found to effectively catalyze the reaction.…”
Section: Introductionmentioning
confidence: 99%